Learning Management, Competitive Strategy of Jiangsu Zhong Nong Ke Company - Worapongpat, Ntapat; Song, Ming (Journal of Education and Learning Reviews, 2025)
Background and Aim: The functional food industry has seen rapid growth in recent years, driven by increasing consumer awareness of health and wellness benefits. As consumer demands evolve, companies like Jiangsu ZhongNongKe Food Engineering Co., Ltd. are challenged to develop competitive strategies that align with shifting market preferences. This study aims to assess Jiangsu ZhongNongKe’s market positioning by applying the 4P theory, focusing on product differentiation, competitive pricing, strategic promotion, and enhanced distribution channels. By identifying key factors influencing purchasing behavior and understanding competitor strategies, this research seeks to provide Jiangsu ZhongNongKe with a sustainable competitive advantage in the functional food market. Materials and Methods: A mixed-methods approach was utilized in this study. Data collection involved both qualitative and quantitative methods: in-depth interviews were conducted with members of Jiangsu ZhongNongKe’s executive team to understand strategic perspectives, while a structured questionnaire was distributed to 400 domestic customers. The questionnaire focused on factors influencing purchasing decisions, perceptions of product quality, pricing sensitivity, and brand loyalty. Data were analyzed using descriptive statistics for quantitative insights and content analysis for qualitative responses, providing a comprehensive view of consumer behaviors and market positioning. Results: The analysis revealed that customer-centered product development and differentiated, high-quality functional foods significantly increase market awareness and brand competitiveness. Flexible pricing strategies tailored to customer demand were found to enhance product price competitiveness and market share. Additionally, establishing a strong online and offline presence through new media marketing and partnerships with health-focused institutions proved effective in boosting brand visibility and penetration. Lastly, experiential and relationship marketing, along with a VIP membership system, were shown to increase customer loyalty and engagement. Conclusion: Jiangsu ZhongNongKe can achieve a sustainable competitive advantage by implementing a customer-centric strategy that emphasizes quality, flexibility in pricing, and diversified promotional approaches. By prioritizing consumer needs and leveraging strategic partnerships, the company is positioned to strengthen its market reputation and solidify its standing in the functional food industry. Future growth will be supported by continuously adapting to market trends and enhancing customer engagement through innovative marketing practices.